Dynamics of changes of antioxidant system indexes during the growth of two Lewis lung carcinoma variants - Pyaskovskaya, O.N.; Sorokina, L.V.; Kolesnik, D.L.; Boichuk, I.V.; Melnikov, O.R.; Solyanik, G.I. (Experimental Oncology, 2014)
Aim: To study an intensity of prooxidant processes and activity of antioxidant enzymes in tumor tissue of two Lewis lung carcinoma variants (LLC and LLC/R9) differing by their proliferative, metastatic, and angiogenic potential (LLC/R9 as compared to LLC is characterized by lower metastatic activity, higher proliferative and angiogenic potential). Materials and Methods: The in vitro study was carried out using cultured LLC and LLC/R9 cell lines, and in vivo on 50 female С57/BL6 mice. The indexes of prooxidant processes and activity of antioxidant enzymes have been studied using the methods of experimental oncology, optical spectroscopy, fluorescent spectroscopy, electron paramagnetic resonance, statistical analysis. Results: There has been determined the coherence of results on 1.5 fold higher (p < 0.01) level of spontaneous generation of reactive oxygen species (ROS) by LLC cells in vitro compared to LLC/R9 cells, and twice (p < 0.05) higher content of secondary products of lipid peroxidation at 14th and 17th day of tumor growth in LLC compared to that in LLC/R9. It has been shown that deficiency of nutrient substrates determines an increase (p < 0.01) of ROS production in LLC/R9 cells what is in congruence with the data on accumulation of nitrosyl complexes of heme iron in mitochondria of LLC/R9 during tumor growth. Activity of superoxide dismutase during tumor growth has altered in unmonotonous way: starting from 14th day of growth it sharply increased by 147% (17th day, LLC) and 217% (20th day, LLC/R9), and then decreased to the level registered at 14th day. Progressive decrease of activity of glutathione peroxidase (GP) and glutathione-S-transferase (GST) during LLC growth has been accompanied with the decrease of the level of reduced glutathione (GSH) by 70% (p < 0.05). In the case of LLC/R9 the decrease of GP activity at initial stages of tumor growth correlated with significant increase of GSH level in the tumor — by 250% (p < 0.01). It has been shown that in LLC/R9 tumors (unlike to LLC), GSH utilization is mostly provided by GST, its significantly higher activity has been detected in LLC/R9 tumors compared to LLC. Conclusion: We have revealed a number of peculiarities of antioxidant system functioning in LLC and LLC/R9 tumors and have shown a relation between an activity of antioxidant system and some biological properties of studied tumor variants. Key Words: Lewis lung carcinoma variants, reactive oxygen species, lipid peroxidation, antioxidant enzymes, glutathione dependent enzymes.